Studying Acetylation of Aconitase Isozymes by Genetic Code Expansion - Araujo, Jessica; Ottinger, Sara; Venkat, Sumana; Gan, Qinglei; Fan, Chenguang (Frontiers in Chemistry, 2022)
Aconitase catalyzes the second reaction of the tricarboxylic acid cycle, the reversible conversion of citrate and isocitrate. Escherichia coli has two isoforms of aconitase, AcnA and AcnB. Acetylomic studies have identified acetylation at multiple lysine sites of both E. coli aconitase isozymes, but the impacts of acetylation on aconitases are unknown. In this study, we applied the genetic code expansion approach to produce 14 site-specifically acetylated aconitase variants. Enzyme assays and kinetic analyses showed that acetylation of AcnA K684 decreased the enzyme activity, while acetylation of AcnB K567 increased the enzyme activity. Further in vitro acetylation and deacetylation assays were performed, which indicated that both aconitase isozymes could be acetylated by acetyl-phosphate chemically, and be deacetylated by the CobB deacetylase at most lysine sites. Through this study, we have demonstrated practical applications of genetic code expansion in acetylation studies.